Ban on Sale of Loose Cigarettes: Awareness, Perceptions and Practices among Vendors and Smokers in Karnataka, India - K, Eshwari; M Kulkarni, Muralidhar; Bhagawath, Rohith; Mullapudi, Somya; Selvarajan, Tarun; Kamath, Veena (Indian Journal of Community Health, 2020)
Background: The Government of Karnataka banned loose cigarettes sale effect from September 2017 and is punishable under Cigarettes and Other Tobacco Products Act (COTPA) with fine and imprisonment in case of violation. Aim & Objective: Study aims to assess awareness, perceptions and practices about ban among tobacco vendors and smokers. Methods and Material: Cross sectional survey was carried using pre-tested questionnaire to collect information regarding awareness about ban among vendors and smokers. Data were analyzed using SPSS version 15.0. Results: Ninety-five percent of the tobacco vendors continued to sell loose cigarettes despite the ban. Among vendors, 49.7%, were aware of ban and of them 53.5% knew it is a punishable offense. Vendors opined that they would stop selling loose cigarettes if ban is strictly enforced with frequent checks on periodical basis. One-fourth smokers opined they will reduce cigarettes consumption with few making an attempt to quit. Conclusions: Awareness about ban on sale of loose cigarettes was unsatisfactory among vendors and smokers including lack of knowledge regarding legal actions in case of violation. However, vendors responded favorably towards obeying the law. Smokers are likely to reduce or even quit smoking if the law is strictly enforced which highlights the need for creating awareness drives and strong enforcement of the policy.